2010
DOI: 10.3928/1081597x-20101215-02
|View full text |Cite
|
Sign up to set email alerts
|

LASIK Flap Creation With the Ziemer Femtosecond Laser in 787 Consecutive Eyes

Abstract: The Ziemer FEMTO LDV laser created thinner LASIK flaps than intended but with a low standard deviation and minimal intraoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…In our previous study, when we used the reusable FEMTO LDV suction ring in 787 eyes, flap thickness averaged 90.0 ± 5.0 mm. 6 In it, the first and second cut flaps did not differ significantly (right eye 90.0 ± 5.5 mm vs left eye 90.1 ± 4.6 mm). Thus, both reusable and disposable suction rings gave similar results for flap characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study, when we used the reusable FEMTO LDV suction ring in 787 eyes, flap thickness averaged 90.0 ± 5.0 mm. 6 In it, the first and second cut flaps did not differ significantly (right eye 90.0 ± 5.5 mm vs left eye 90.1 ± 4.6 mm). Thus, both reusable and disposable suction rings gave similar results for flap characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…6 Increasing flap thickness was associated with increasing corneal thickness and flatter keratometric value. Furthermore, we found that increasing flap diameter was associated with thinner flap thickness in myopic eyes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations